Діяльність державних архівів західних областей України з виявлення документів, що містять інформацію про трагедію українського народу 1932–1933 років - Хаварівський, Б. (Архіви України, 2008)
The materials highlight the activities of “Ukrainian Archivists’ Contribution to Revival of Historical Memory” inter-agency meeting (on occasion of the 75th anniversary of the 1932–1933 Famine in Ukraine), held on November 18, 2008, in Kyiv. The publication summarizes the outcomes of the efforts aimed at expanding documentary and support basis of the 1932–1933 Famine in Ukraine, which were undertaken in early 1990s. It also includes the reports of the Directors of the State Archives of Donets’k, Mykolaiv, Ternopil’, Chernihiv oblasts on key areas of the given activities.